Radiobiological effects of multiple vs. single low-doses pre-irradiation on HT29 cell line - Djan, Igor; Solajic, Slavica; Djan, Mihajla; Vucinic, Natasa; Popovic, Dunja; Ilic, Miroslav; Lučić, Silvija; Bogdanovic, Gordana (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study was to compare radiobiological effects of multiple vs. single low-dose pre-irradiation on the HT29 cell line. This regime is designed to be as similar as possible to fractionated tumour radiotherapy treatment, and to provide data on radiobiological effects on human tumour cells. Material and methods : The cell line used in the study was HT29 (human colorectal adenocarcinoma, American Type Culture Collection HTB-38 ™ ). Also, for comparison, the MRC5 cell line (human foetal lung fibroblasts, American Type Culture Collection CCL 171) was used. Four-day treatment in a 4 × 2 Gy regime was performed. Cell viability was evaluated by tetrazolium colorimetric MTT assay. Results : Multiple low-dose pre-irradiation induced a stronger radioadaptive response compared to single low-dose application in the HT29 cell line. Multiple pre-irradiation with 0.03 Gy and 0.05 Gy caused radioadaptive effects, while in both single and multiple low-dose pre-irradiation regimes 0.07 Gy led to radiosensitivity. Radiobiological effects induced in the HT29 cell line by low-dose pre-irradiation were evidently weak during the treatment time, because a single low-dose applied only on the first day gave no radioadaptive effects. In the MRC5 cell line different effects were registered, since radioadaptive response has not been observed after multiple or single pre-irradiation. Conclusions : The obtained data are interesting, especially for the possible application of low-dose pre-irradiation in radiotherapy.